Advances in Diagnostics and Drug Discovery against Resistant and Latent Tuberculosis Infection - Shleider Carnero Canales, Christian; Marquez Cazorla, Jessica; Furtado Torres, André Henrique [UNESP]; Monteiro Filardi, Eloise T. [UNESP]; Di Filippo, Leonardo Delello [UNESP]; Costa, Paulo Inácio [UNESP]; Roque-Borda, Cesar Augusto [UNESP]; Pavan, Fernando Rogério [UNESP] (My University, 2023)
Latent tuberculosis infection (LTBI) represents a subclinical, asymptomatic mycobacterial state affecting approximately 25% of the global population. The substantial prevalence of LTBI, combined with the risk of progressing to active tuberculosis, underscores its central role in the increasing incidence of tuberculosis (TB). Accurate identification and timely treatment are vital to contain and reduce the spread of the disease, forming a critical component of the global strategy known as “End TB.” This review aims to examine and highlight the most recent scientific evidence related to new diagnostic approaches and emerging therapeutic treatments for LTBI. While prevalent diagnostic methods include the tuberculin skin test (TST) and interferon gamma release assay (IGRA), WHO’s approval of two specific IGRAs for Mycobacterium tuberculosis (MTB) marked a significant advancement. However, the need for a specific test with global application viability has propelled research into diagnostic tests based on molecular diagnostics, pulmonary immunity, epigenetics, metabolomics, and a current focus on next-generation MTB antigen-based skin test (TBST). It is within these emerging methods that the potential for accurate distinction between LTBI and active TB has been demonstrated. Therapeutically, in addition to traditional first-line therapies, anti-LTBI drugs, anti-resistant TB drugs, and innovative candidates in preclinical and clinical stages are being explored. Although the advancements are promising, it is crucial to recognize that further research and clinical evidence are needed to solidify the effectiveness and safety of these new approaches, in addition to ensuring access to new drugs and diagnostic methods across all health centers. The fight against TB is evolving with the development of more precise diagnostic tools that differentiate the various stages of the infection and with more effective and targeted treatments. Once consolidated, current advancements have the potential to transform the prevention and treatment landscape of TB, reinforcing the global mission to eradicate this disease.
Keywords: diagnostic; Drug discovery; Latent tuberculosis infection; Mycobacterium tuberculosis